2013
DOI: 10.35952/jik.v2i4.63
|View full text |Cite
|
Sign up to set email alerts
|

Perhatian Keluarga Menurunkan Frekuensi Kekambuhan Pada Pasien Skizofrenia

Abstract: Peran keluarga dalam bentuk dukungan perhatian sangat penting terhadap pasien gangguan jiwa, karena keluarga adalah system pendukung utama yang memberikan perawatan langsung pada klien, bila keluarga memahami kebutuhan anggotanya, maka keluarga akan memberikan dukungan untuk keberhasilan dalam pengobatan. Jenis penelitian ini kuantitatif dengan pendekatan Cross Sectional, tehnik sampling menggunakan accidental sampling. Data dikumpulkan menggunakan kuesioner, Uji hipotesis bivariat menggunakan Chi square. Hasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(Lestari, 2019), reported that within 6 months after treatment, 30%-40% of patients had a relapse, whereas after 1 year after treatment 40%-50% of patients had a relapse, from 3-5 years after treatment, 65% were found. -75% of patients experience a relapse (Rahmawati, 2013). Based on the results of the study, 25% to 50% of clients who return home from the hospital do not take medication regularly (Rasmun, 2017)…”
Section: Introductionmentioning
confidence: 95%
“…(Lestari, 2019), reported that within 6 months after treatment, 30%-40% of patients had a relapse, whereas after 1 year after treatment 40%-50% of patients had a relapse, from 3-5 years after treatment, 65% were found. -75% of patients experience a relapse (Rahmawati, 2013). Based on the results of the study, 25% to 50% of clients who return home from the hospital do not take medication regularly (Rasmun, 2017)…”
Section: Introductionmentioning
confidence: 95%